Preparation method of two-photon coupled nickel-cobalt-sulfur-based supercapacitor electrode
By growing a ternary composite structure of graphite phase carbon nitride and nitrogen-doped carbon quantum dots on the surface of the nickel-cobalt sulfur-based supercapacitor electrode, the problem of low energy density of the supercapacitor is solved, and a significant improvement in specific capacitance and enhanced photoelectric conversion efficiency are achieved.
Patent Information
- Application Number
- CN202411750031.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-25
AI Technical Summary
The low energy density of supercapacitors limits their applications in the fields of energy storage and conversion.
By hydrothermal growth of graphite phase carbon nitride (g-C3N4) and nitrogen-doped carbon quantum dots (NCQDs) on the surface of the nickel-cobalt sulfur-based supercapacitor electrode, a ternary composite structure with energy level adaptation is formed, and the specific capacitance of the electrode material is improved by using the photophysics field.
The specific capacitance of the supercapacitor electrode material is significantly improved, the photoelectric conversion efficiency of the photo-assisted supercapacitor is enhanced, and the effective utilization of solar energy is promoted.
Smart Images

Figure CN119503910A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoelectrochemistry and nanomaterials, and in particular relates to a method for preparing a two-photon coupled nickel-cobalt-sulfur-based supercapacitor electrode. Background Art
[0002] The effective use of green energy and sustainable energy has become an important means to solve the energy crisis, and the development of related energy storage equipment is a top priority. Supercapacitors have a long cycle life, fast charge and discharge efficiency, and high power density, and play an important role in addressing energy and environmental issues. However, the low energy density of supercapacitors remains a problem that needs to be solved. In recent years, most research has been done to improve the energy density of supercapacitors by microscopic morphology control of electrode materials, defect engineering control, and functional composites between compounds.
[0003] Recently, the emergence of light-assisted charging and energy storage devices has provided an effective way to achieve solar energy intervention in energy conversion and storage. Combining light drive with supercapacitors, semiconductor materials are used to generate photogenerated electrons and holes through light absorption to participate in the charging and discharging process, so as to improve the efficiency of energy conversion and charge storage, promote electrochemical charge storage, and enhance its energy density. Therefore, constructing a photoelectrode system with high specific capacitance, high energy density, and simultaneous light collection and energy storage characteristics has important scientific value and practical significance for realizing solar energy conversion and storage.
[0004] Binary transition metal sulfide (NiCo2S4) has high electronic conductivity, multi-charge redox activity, light-assisted enhancement effect and excellent stability, making it a promising photoresponsive energy storage material. Graphitic carbon nitride (g-C3N4) can efficiently absorb visible light, with a band gap of about 2.7 eV. It can generate photogenerated electrons and holes under light irradiation, participate in electrode redox reactions, accelerate reaction kinetics, and improve electrochemical performance. In addition, its surface is rich in active groups such as amino and imine groups, which can further promote electron transport and ion diffusion. Nitrogen-doped carbon quantum dots (NCQDs) can efficiently absorb ultraviolet to visible light and have excellent fluorescence properties. This light absorption and photogenerated electron transfer ability make it suitable for light-assisted energy storage. Secondly, the rich functional groups on the surface not only enable it to have a strong interfacial interaction with transition metal compounds, but also enhance the interfacial electron transport capacity and the cycle stability of electrode materials. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an energy-level-matched ternary composite electrode material and its application, by hydrothermally growing a semiconductor material g-C3N4 with photosensitivity and nitrogen-doped carbon quantum dots (NCQDs) on the surface of NiCo2S4 to form an energy-level-matched ternary composite structure, driven by a photophysical field, to improve the specific capacitance of the supercapacitor electrode material, thereby solving the key problem of the low energy density of the supercapacitor.
[0006] The purpose of the present invention can be achieved through the following technical solutions: The first aspect of the present invention discloses a method for preparing a two-photon coupled nickel-cobalt-sulfur-based supercapacitor electrode, comprising the following steps: Step S1: First, the nickel foam is ultrasonically cleaned in ethanol and water respectively, and then ultrasonically cleaned in a dilute hydrochloric acid solution, and then rinsed with dilute hydrochloric acid and placed in a vacuum drying oven for drying.
[0007] Step S2: Place melamine in a crucible, seal it with aluminum foil, and place it in a tubular furnace with air for calcination. After cooling it to room temperature, grind the blocky g-C3N4 repeatedly in a mortar to form a fine powder.
[0008] Step S3: Add citric acid and ethylenediamine into deionized water and stir evenly, then put the mixed solution into a reactor for hydrothermal reaction, and wait for it to cool to natural room temperature to obtain NCQDs.
[0009] Step S4: immerse the nickel foam treated in S1 in a mixed solution of nickel nitrate hexahydrate, cobalt nitrate hexahydrate and thiourea for hydrothermal reaction, wait for it to cool to natural room temperature, and wash and dry it to obtain a NiCo2S4 / NF composite electrode material.
[0010] Step S5: Place the g-C3N4 powder in S2 and the NCQDs in S3 in a mixture of water and ethylene glycol and stir them evenly to form a mixed solution.
[0011] Step S6: Immerse the electrode material obtained in S4 into the mixed solution of S5 for hydrothermal reaction, wait for it to cool to natural room temperature, and wash and dry it to obtain a NiCo2S4@g-C3N4@NCQDs / NF composite electrode material.
[0012] The size of the nickel foam in S1 is (5-15) mm×(30-50) mm×0.5 mm. More preferably, the size of the nickel foam is 10 mm×40 mm×0.5 mm.
[0013] Preferably, the ethanol used in S1 is 99.7% anhydrous ethanol, the water is deionized water, and the concentration of dilute hydrochloric acid is 2 mol L -1The ultrasonic time in water and ethanol was 20 min, the ultrasonic time in dilute hydrochloric acid was 5 min, the vacuum drying oven temperature was 60 °C, and the drying time was 24 h.
[0014] Preferably, the temperature of the melamine heat treatment in S2 is 550 °C, the heat treatment time is 2 h, and the grinding time is 4 h.
[0015] Preferably, in S3, the citric acid content is 1-3 mg, the ethylenediamine content is 1-2 ml, and the deionized water capacity is 40-60 ml.
[0016] Preferably, the ratio of nickel nitrate hexahydrate, cobalt nitrate hexahydrate and thiourea in S4 is 0.8-1.2 mmol:1.8-2.2 mmol:3.6-4.4 mmol, and more preferably, the ratio of nickel nitrate hexahydrate, cobalt nitrate hexahydrate and thiourea is 1 mmol:2 mmol:4 mmol.
[0017] Preferably, the amount of g-C3N4 used in S5 is 10-30 mg, and the amount of NCQDs used is 1-3 ml.
[0018] Preferably, the mixed solutions in S4 and S5 both include ethylene glycol and deionized water, wherein the amount of ethylene glycol and deionized water used in S4 is 40-80 ml, and the volume ratio is 1:1; the amount of ethylene glycol and deionized water used in S5 is 20-50 ml, and the volume ratio is 1:1.
[0019] Preferably, the hydrothermal reaction temperature of S3 is 160-200 °C, and the time is 4-6 h; the hydrothermal reaction temperature of S4 is 100-120 °C, and the time is 22-26 h; the hydrothermal reaction temperature of step S6 is 140-180 °C, and the time is 8-12 h.
[0020] Preferably, in S3, citric acid and ethylenediamine are fully dissolved in deionized water, and the stirring time is 10-20 min; in S4, nickel nitrate hexahydrate, cobalt nitrate hexahydrate and thiourea are fully dissolved in a mixed solution of deionized water and ethylene glycol, and the stirring time is 40-70 min; in S5, g-C3N4 and NCQDs are fully dissolved in a mixed solution of deionized water and ethylene glycol, and the stirring time is 20-40 min.
[0021] Preferably, the washing is cross-washing with anhydrous ethanol and deionized water for 3-6 times; the drying condition is vacuum drying at a temperature of 60° C. for 8-12 h.
[0022] In the above-mentioned applications, the energy storage characteristics of any of the NiCo2S4@g-C3N4@NCQDs / NF composite electrodes in light-driven supercapacitors were tested in a three-electrode system.
[0023] In the above application, the three-electrode system is: NiCo2S4@g-C3N4@NCQDs / NF composite electrode as the working electrode, saturated Ag / AgCl as the reference electrode, Pt sheet as the counter electrode, and 3M KOH as the electrolyte solution.
[0024] For the above application, the illumination conditions are: 100 mW cm -2 A xenon lamp is used as the light source, and a filter less than 420 nm controls the wavelength range of the incident light to the visible light region.
[0025] The second aspect of the present invention discloses a method for preparing a two-photon coupled nickel-cobalt-sulfur-based supercapacitor electrode, which is prepared by any of the above-mentioned preparation methods.
[0026] The third aspect of the present invention discloses an application of a two-photon coupled nickel-cobalt-sulfur based supercapacitor composite electrode.
[0027] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention has a simple method for preparing electrode materials, low-cost raw materials and is green and environmentally friendly. The composite material is prepared by calcination and hydrothermal methods, which greatly improves the electrochemical performance of the material and has good application prospects in the fields of photoelectrochemistry and nanomaterial technology.
[0028] 2. In the present invention, NiCo2S4@g-C3N4@NCQDs / NF is selected as the electrode material. NiCo2S4 itself has a high theoretical specific capacity, and the addition of g-C3N4 and NCQDs can further increase the specific surface area of the electrode material, provide more active sites, and thus improve the overall specific capacity. At the same time, the introduction of g-C3N4 and CQDs can reduce the agglomeration of active substances and further improve the cycle stability.
[0029] 3. In the present invention, g-C3N4 and NCQDs are selected as two-photon synergistic units. g-C3N4 is an efficient photocatalyst that can absorb visible light and generate photogenerated electron-hole pairs. These photogenerated carriers can participate in electrochemical reactions and improve the energy density and power density of capacitors. At the same time, NCQDs have good light capture ability and high photoluminescence efficiency, which can form a synergistic effect with g-C3N4, further enhance the light response performance, and improve the photoelectric conversion efficiency of light-assisted supercapacitors.
[0030] 4. The present invention designs a new type of light-assisted supercapacitor, provides a new idea for the development of photosensitive energy devices, and promotes the effective use of solar energy.
[0031] 5. The present invention innovatively introduces light drive, which improves the specific capacitance of the supercapacitor through sunlight irradiation. Under light conditions, 1 A g -1 The specific capacitance of the material is 2836 F g -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Under light conditions, the different electrode materials in Examples 1, 2, 3, 4, and 5 have a voltage drop of 10 mV s -1 Comparison of cyclic voltammetry (CV) curves.
[0033] Figure 2 Under light conditions, different electrode materials in Examples 1, 2, 3, 4, and 5 are -1 Comparison chart of constant current charge and discharge (GCD) at .
[0034] Figure 3 It is a comparison diagram of electrochemical impedance spectroscopy (EIS) of different electrode materials in Examples 1, 2, 3, 4, and 5 under light conditions.
[0035] Figure 4 The results are as follows: Under the condition of no light, the different electrode materials in Examples 1, 2, 3, 4, and 5 are at 10 mV s -1 Comparison of cyclic voltammetry (CV) curves.
[0036] Figure 5 Under the condition of no light, the different electrode materials in Examples 1, 2, 3, 4, and 5 are -1 Comparison chart of constant current charge and discharge (GCD) at .
[0037] Figure 6 It is a comparison diagram of electrochemical impedance spectra (EIS) of different electrode materials in Examples 1, 2, 3, 4, and 5 under the condition of no light.
[0038] Figure 7 The NiCo2S4@g-C3N4@NCQDs / NF and NiCo2S4 / NF in Examples 1 and 4 under light and without light at 10 mV s -1 Comparison of cyclic voltammetry (CV) curves.
[0039] Figure 8 The NiCo2S4@g-C3N4@NCQDs / NF and NiCo2S4 / NF in Examples 1 and 4 under the conditions of light and without light are shown in Table 1.-1 Comparison chart of constant current charge and discharge (GCD) at .
[0040] Fig. 9 The NiCo2S4@g-C3N4@NCQDs / NF and NiCo2S4 / NF in Examples 1 and 4 under the conditions of light and without light are shown in Table 1. -1 Comparison of electrochemical impedance spectroscopy (EIS) at 400 nm and 800 nm. DETAILED DESCRIPTION
[0041] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several optimizations and improvements can also be made without departing from the concept of the present invention. The above all belong to the protection scope of the present invention.
[0042] In the following embodiments, except that the test used in the present invention is Chenhua electrochemical workstation CHI660E, and the solar illumination simulator is LP-750 adjustable photocatalyst; the other raw materials or processing technologies such as nickel foam (NF), nickel nitrate hexahydrate, cobalt nitrate hexahydrate, thiourea, melamine, citric acid, ethylenediamine, etc., unless otherwise specified, indicate that they are conventional commercially available products or conventional processing technologies in the field.
[0043] Example 1 A method for preparing a NiCo2S4@g-C3N4@NCQDs / NF composite electrode material is as follows: S1: Weigh 30 mL of ethylene glycol and 30 mL of deionized water into a 100 mL beaker, then weigh 0.1454 g of nickel nitrate hexahydrate, 0.2910 g of cobalt nitrate hexahydrate, and 0.1522 g of thiourea and transfer them to the beaker. Stir thoroughly with a magnetic stirrer for 50 min to obtain solution A. Pour 60 mL of the mixed solution evenly into three reactors, transfer the treated nickel foam into the reactor, tighten it, and perform a hydrothermal reaction. The temperature is set to 110 °C and the hydrothermal time is 24 h. Wait for the reactor to cool to room temperature, take out the sample for washing and vacuum drying, and the NiCo2S4 / NF electrode material can be obtained.
[0044] S2: Weigh 0.8 g of melamine powder into a crucible and seal it with aluminum foil, then put it into a muffle furnace and calcine it at 550 °C for 2 h. After it cools to room temperature, a light yellow block is formed on the surface of the crucible. Take it out with a spoon and put it into a mortar for grinding for 4 h to form powdered g-C3N4.
[0045] S3: Weigh 50 mL of deionized water into a 100 mL beaker, then weigh 2 g of citric acid and 1.5 mL of ethylenediamine solution, and stir thoroughly with a magnetic stirrer for 15 min to obtain solution B. Transfer the solution to a reactor and perform a hydrothermal reaction at 180 °C for 5 h, and wait for the reactor to cool to room temperature to obtain NCQDs.
[0046] S4: Weigh 20 mg of g-C3N4 prepared in S2 and 2 mL of NCQDs prepared in S3, dissolve them in a mixture of 20 mL of water and 20 mL of ethylene glycol, and stir them thoroughly with a magnetic stirrer for 30 min to obtain solution C. Then immerse the NCS / NF prepared in S1 in solution C and transfer it to a reactor for hydrothermal reaction at a temperature of 160°C for 10 h. Wait for the reactor to cool to room temperature, take out the sample for washing and vacuum drying, and obtain NiCo2S4@g-C3N4@NCQDs / NF electrode material.
[0047] The NiCo2S4@g-C3N4@NCQDs / NF electrode material prepared by S4 was used as the working electrode, Ag / AgCl as the reference electrode, and platinum wire as the counter electrode.
[0048] The electrode materials were subjected to cyclic voltammetry test, constant current charge-discharge test and electrochemical impedance test by using Chenhua CHI660E electrochemical workstation. The working electrode, counter electrode and reference electrode were connected to the electrochemical workstation and the reaction mixture was stirred at 3 mol L -1 The samples were tested in KOH solution. First, the samples were activated by cyclic voltammetry test, and then the electrochemical performance test was performed after stabilization to obtain the performance curve without light exposure. Then, the samples with the same process parameters were replaced, activated, and the NiCo2S4@g-C3N4@NCQDs / NF electrode material was irradiated with light source for 20 min by LP-750 adjustable photocatalytic instrument, and then the performance of the samples was tested by electrochemical workstation. The electrode material was 1 A g -1 At a current density of 1.5 Å, the specific capacitance in dark conditions reached 1932 F g -1 After photovoltaic irradiation, the specific capacitance of the material reached 2836 F g at the same current density. -1 .
[0049] Example 2 A method for preparing a NiCo2S4@NCQDs / NF composite electrode material is as follows: S1: Weigh 30 mL of ethylene glycol and 30 mL of deionized water into a 100 mL beaker, then weigh 0.1454 g of nickel nitrate hexahydrate, 0.2910 g of cobalt nitrate hexahydrate, and 0.1522 g of thiourea and transfer them to the beaker. Stir thoroughly with a magnetic stirrer for 50 min to obtain solution A. Pour 60 mL of the mixed solution evenly into three reactors, transfer the treated nickel foam into the reactor, tighten it, and perform a hydrothermal reaction. The temperature is set to 110 °C and the hydrothermal time is 24 h. Wait for the reactor to cool to room temperature, take out the sample for washing and vacuum drying, and the NiCo2S4 / NF electrode material can be obtained.
[0050] S2: Weigh 50 mL of deionized water into a 100 mL beaker, then weigh 2 g of citric acid and 1.5 mL of ethylenediamine solution, and stir thoroughly with a magnetic stirrer for 15 min to obtain solution B. Transfer the solution to a reactor and perform a hydrothermal reaction at 180 °C for 5 h, and wait for the reactor to cool to room temperature to obtain NCQDs.
[0051] S3: Weigh 2 mL of NCQDs prepared in S2, dissolve it in a mixture of 20 mL of water and 20 mL of ethylene glycol, and stir it thoroughly with a magnetic stirrer for 30 min to obtain solution B. Then immerse the NCS / NF prepared in S1 in solution B and transfer it to the reactor for hydrothermal reaction at a temperature of 160 °C for 10 h. Wait for the reactor to cool to room temperature, take out the sample for washing and vacuum drying, and obtain NiCo2S4@NCQDs / NF electrode material.
[0052] The NiCo2S4@NCQDs / NF electrode material prepared by S3 was used as the working electrode, Ag / AgCl as the reference electrode, and platinum wire as the counter electrode.
[0053] The electrode materials were subjected to cyclic voltammetry test, constant current charge-discharge test and electrochemical impedance test by using Chenhua CHI660E electrochemical workstation. The working electrode, counter electrode and reference electrode were connected to the electrochemical workstation and the reaction mixture was stirred at 3 mol L -1 The samples were tested in KOH solution. First, the samples were activated by cyclic voltammetry test, and then the electrochemical performance test was performed after stabilization to obtain the performance curve without light exposure. Then, the samples with the same process parameters were replaced, activated, and the NiCo2S4@NCQDs / NF electrode material was irradiated with light for 20 min by LP-750 adjustable photocatalytic instrument, and then the performance of the samples was tested by electrochemical workstation. The electrode material was 1 A g -1 At a current density of 1.5 Å, the specific capacitance in dark conditions reached 1721 F g-1 After photovoltaic irradiation, the specific capacitance of the material reached 2135 F g at the same current density. -1 .
[0054] Example 3 A method for preparing a NiCo2S4@g-C3N4 / NF composite electrode material is as follows: S1: Weigh 30 mL of ethylene glycol and 30 mL of deionized water into a 100 mL beaker, then weigh 0.1454 g of nickel nitrate hexahydrate, 0.2910 g of cobalt nitrate hexahydrate, and 0.1522 g of thiourea and transfer them to the beaker. Stir thoroughly with a magnetic stirrer for 50 min to obtain solution A. Pour 60 mL of the mixed solution evenly into three reactors, transfer the treated nickel foam into the reactor, tighten it, and perform a hydrothermal reaction. The temperature is set to 110 °C and the hydrothermal time is 24 h. Wait for the reactor to cool to room temperature, take out the sample for washing and vacuum drying, and the NiCo2S4 / NF electrode material can be obtained.
[0055] S2: Weigh 0.8 g of melamine powder into a crucible and seal it with aluminum foil, then put it into a muffle furnace and calcine it at 550 °C for 2 h. After it cools to room temperature, a light yellow block is formed on the surface of the crucible. Take it out with a spoon and put it into a mortar for grinding for 4 h to form powdered g-C3N4.
[0056] S3: Weigh 20 mg of g-C3N4 prepared in S2, dissolve it in a mixture of 20 mL of water and 20 mL of ethylene glycol, and stir it thoroughly with a magnetic stirrer for 30 min to obtain solution B. Then immerse the NCS / NF prepared in S1 in solution B and transfer it to a reactor for hydrothermal reaction at a temperature of 160 °C for 10 h. Wait for the reactor to cool to room temperature, take out the sample for washing and vacuum drying, and obtain NiCo2S4@g-C3N4 / NF electrode material.
[0057] The NiCo2S4@g-C3N4 electrode material prepared by S3 was used as the working electrode, Ag / AgCl as the reference electrode, and platinum wire as the counter electrode.
[0058] The electrode materials were subjected to cyclic voltammetry test, constant current charge-discharge test and electrochemical impedance test by using Chenhua CHI660E electrochemical workstation. The working electrode, counter electrode and reference electrode were connected to the electrochemical workstation and the reaction mixture was stirred at 3 mol L -1The samples were tested in KOH solution. First, the samples were activated by cyclic voltammetry test, and then the electrochemical performance test was performed after stabilization to obtain the performance curve without light exposure. Then, the samples with the same process parameters were replaced, activated, and the NiCo2S4@g-C3N4 / NF electrode material was irradiated with light for 20 min by LP-750 adjustable photocatalytic instrument, and then the performance of the samples was tested by electrochemical workstation. The electrode material was -1 At a current density of 1.3 Å, the specific capacitance in dark conditions reached 1172 F g -1 After photovoltaic irradiation, the specific capacitance of the material reached 1607 F g at the same current density. -1 .
[0059] Example 4 A method for preparing a NiCo2S4 / NF electrode material is as follows: S1: Weigh 30 mL of ethylene glycol and 30 mL of deionized water into a 100 mL beaker, then weigh 0.1454 g of nickel nitrate hexahydrate, 0.2910 g of cobalt nitrate hexahydrate, and 0.1522 g of thiourea and transfer them to the beaker. Stir thoroughly with a magnetic stirrer for 50 min to obtain solution A. Pour 60 mL of the mixed solution evenly into three reactors, transfer the treated nickel foam into the reactor, tighten it, and perform a hydrothermal reaction. The temperature is set to 110 °C and the hydrothermal time is 24 h. Wait for the reactor to cool to room temperature, take out the sample for washing and vacuum drying, and the NiCo2S4 / NF electrode material can be obtained.
[0060] The NiCo2S4 / NF electrode material prepared by S1 was used as the working electrode, Ag / AgCl as the reference electrode, and platinum wire as the counter electrode.
[0061] The electrode materials were subjected to cyclic voltammetry test, constant current charge-discharge test and electrochemical impedance test by using Chenhua CHI660E electrochemical workstation. The working electrode, counter electrode and reference electrode were connected to the electrochemical workstation and the reaction mixture was stirred at 3 mol L -1 The samples were tested in KOH solution. First, the samples were activated by cyclic voltammetry test, and then the electrochemical performance test was performed after stabilization to obtain the performance curve without light exposure. Then, the samples with the same process parameters were replaced, activated, and the NiCo2S4 / NF electrode material was irradiated with light source for 20 min by LP-750 adjustable photocatalytic instrument, and then the performance of the samples was tested by electrochemical workstation. -1 At a current density of 1.5 Å, the specific capacitance in dark conditions reached 902 F g -1 After photovoltaic irradiation, the specific capacitance of the material reached 1364 F g at the same current density.-1 .
[0062] Example 5 A method for preparing a g-C3N4 / NF electrode material is as follows: S1: Weigh 0.8 g of melamine powder into a crucible and seal it with aluminum foil, then put it into a muffle furnace and calcine it at 550 °C for 2 h. After it cools to room temperature, a light yellow block is formed on the surface of the crucible. Take it out with a spoon and grind it in a mortar for 4 h to form powdered g-C3N4.
[0063] S2: Weigh 20 mg of g-C3N4 prepared in S1, dissolve it in a mixture of 20 mL of water and 20 mL of ethylene glycol, and stir it thoroughly with a magnetic stirrer for 30 min to obtain solution A. Then transfer the treated nickel foam and solution A to the reactor, tighten it, and perform a hydrothermal reaction at a temperature of 160 °C for 10 h. Wait for the reactor to cool to room temperature, take out the sample for washing and vacuum drying, and obtain the g-C3N4 / NF electrode material.
[0064] The g-C3N4 / NF electrode material prepared by S2 was used as the working electrode, Ag / AgCl as the reference electrode, and platinum wire as the counter electrode.
[0065] The electrode materials were subjected to cyclic voltammetry test, constant current charge-discharge test and electrochemical impedance test by using Chenhua CHI660E electrochemical workstation. The working electrode, counter electrode and reference electrode were connected to the electrochemical workstation and the reaction mixture was stirred at 3 mol L -1 The samples were tested in KOH solution. First, the samples were activated by cyclic voltammetry test, and then the electrochemical performance test was performed after stabilization to obtain the performance curve without light exposure. Then, the samples with the same process parameters were replaced, activated, and the g-C3N4 / NF electrode material was irradiated with light for 20 min by LP-750 adjustable photocatalytic instrument, and then the performance of the samples was tested by electrochemical workstation. The electrode material was 1 A g -1 At a current density of 1.5 Å, the specific capacitance in dark conditions reached 560 F g -1 After photovoltaic irradiation, the specific capacitance of the material reached 731 F g at the same current density. -1 .
[0066] Table 1 Comparison of specific capacitance of electrode materials of different comparative examples and embodiments under dark and light conditions sample <![CDATA[Specific capacitance before light illumination (F g -1 )]]> <![CDATA[Specific capacitance after light illumination (F g -1 )]]> <![CDATA[Example 1 (NiCo2S4@g-C3N4@NCQDs / NF)]]> 1932 2836 <![CDATA[Example 2 (NiCo2S4@NCQDs / NF)]]> 1721 2135 <![CDATA[Example 3 (NiCo2S4@g-C3N4 / NF)]]> 1172 1607 <![CDATA[Example 4 (NiCo2S4 / NF)]]> 902 1364 <![CDATA[Example 5 (g-C3N4 / NF)]]> 560 731 The present invention realizes the ternary composite of the nickel-cobalt-sulfur intrinsic system through a two-step hydrothermal method, grows g-C3N4 and NCQDs on the surface of nickel-cobalt-sulfur nanosheets, so that a good structure-activity relationship and a matching energy band structure are formed between the materials. The internal electric field appears both inside and outside the material, which increases the amount of charge generated and greatly improves the charge transfer rate and specific capacitance of the electrode material.
[0067] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those familiar with the art can easily make various modifications to the embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a two-photon coupled nickel-cobalt-sulfur-based supercapacitor electrode, characterized in that: The following steps are involved: Step S1: ultrasonically clean the nickel foam in ethanol, water and dilute hydrochloric acid respectively, and then put it into a vacuum drying oven for drying; Step S2: Put melamine into a crucible, seal the crucible with aluminum foil, and then put it into a tube furnace with air for calcination. After cooling to room temperature, block-shaped g-C3N4 is obtained, which is then ground into powder in a mortar; Step S3: adding citric acid and ethylenediamine into deionized water and mixing them for hydrothermal reaction, and cooling the deionized water to natural room temperature to obtain NCQDs; Step S4: immersing the nickel foam pretreated in step S1 into a mixed solution of nickel nitrate hexahydrate, cobalt nitrate hexahydrate and thiourea for hydrothermal reaction, cooling it to natural room temperature, washing and drying it, to obtain a NiCo2S4 / NF composite electrode material; Step S5: placing the g-C3N4 powder in step S2 and the NCQDs in step S3 in a mixture of water and ethylene glycol and stirring to form a mixed solution; Step S6: Immerse the electrode material obtained in step S4 into the mixed solution of step S5 for hydrothermal reaction, wait for it to cool to natural room temperature, and wash and dry it to obtain a NiCo2S4@g-C3N4@NCQDs / NF composite electrode material.
2. The method for preparing a two-photon coupled nickel-cobalt-sulfur-based supercapacitor electrode according to claim 1, characterized in that: In step S1, the ethanol used is 99.7% anhydrous ethanol, the water is deionized water, and the concentration of dilute hydrochloric acid is 2 mol / L -1 The ultrasonic time in water and ethanol was 20 min, the ultrasonic time in dilute hydrochloric acid was 5 min, the vacuum drying oven temperature was 60 °C, and the drying time was 24 h.
3. The method for preparing a two-photon coupled nickel-cobalt-sulfur-based supercapacitor electrode according to claim 1, characterized in that: In step S2, the temperature of the melamine heat treatment is 550°C, the heat treatment time is 2 h, and the grinding time is 4 h.
4. The method for preparing a two-photon coupled nickel-cobalt-sulfur-based supercapacitor electrode according to claim 1, characterized in that: In step S3, the amount of citric acid is 1-3 mg, the amount of ethylenediamine is 1-2 ml, the volume of deionized water is 40-60 ml, the hydrothermal reaction temperature is 160-200 °C, and the reaction time is 4-6 h.
5. The method for preparing a two-photon coupled nickel-cobalt-sulfur-based supercapacitor electrode according to claim 1, characterized in that: In the step S4, the ratio of nickel nitrate hexahydrate, cobalt nitrate hexahydrate and thiourea is 0.8-1.2 mmol:1.8-2.2 mmol:3.6-4.4 mmol, the mixed solution is ethylene glycol and deionized water, the amount of ethylene glycol and deionized water used is 40-80 ml, the volume ratio is 1:1, the hydrothermal reaction temperature is 100-120 ° C, and the time is 22-26 h.
6. The method for preparing a two-photon coupled nickel-cobalt-sulfur-based supercapacitor electrode according to claim 1, characterized in that: In the step S5, the amount of g-C3N4 used is 10-30 mg, the amount of NCQDs used is 1-3 ml, the mixed solution is ethylene glycol and deionized water, the amount of ethylene glycol and deionized water used is 40-80 ml, and the volume ratio is 1:
1.
7. The method for preparing a two-photon coupled nickel-cobalt-sulfur-based supercapacitor electrode according to claim 1, characterized in that: The hydrothermal reaction temperature in step S6 is 140-180 °C and the reaction time is 8-12 h.
8. A method for preparing a two-photon coupled nickel-cobalt-sulfur based supercapacitor electrode according to claims 1-7, characterized in that: In the three-electrode test system, NiCo2S4@g-C3N4@NCQDs / NF electrode was used as the photo-assisted electrode for illumination and testing.
9. The method for preparing a two-photon coupled nickel-cobalt-sulfur-based supercapacitor electrode according to claim 8, characterized in that: The three-electrode test system is as follows: NiCo2S4@g-C3N4@NCQDs / NF electrode is used as the working electrode, Pt sheet is used as the counter electrode, saturated Ag / AgCl electrode is used as the reference electrode, 3M KOH is used as the electrolyte solution, and the illumination conditions are as follows: 100 mWcm -2 A xenon lamp is used as the light source, and a filter less than 420 nm controls the wavelength range of the incident light to the visible light region.
10. Application of a two-photon coupled nickel-cobalt-sulfur-based supercapacitor composite electrode, characterized in that: A method for preparing a two-photon coupled nickel-cobalt-sulfur-based supercapacitor electrode as described in any one of claims 1 to 9, wherein the two-photon coupled nickel-cobalt-sulfur-based supercapacitor composite electrode is applied to the field of photoelectrochemical energy storage.